TextGuard: Identifying and Neutralizing Adversarial Threats in Textual Data - Albtsoh, Luay; Omar, Marwan (Universitas Komputer Indonesia, 2025)
Adversarial attacks inside the text domain pose a serious risk to the integrity of Natural Language Processing (NLP) systems. In this study, we propose